PELATIHAN PENYELESAIAN SOAL-SOAL STRUCTURE AND WRITTEN EXPRESSION BEREKUIVALENSI TOEFL PADA SISWA SMK TELKOM PEKANBARU - Qori Islami Aris; Essy Syam (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
In this program, the community service team will provide strategies or tips in solving each problem in the Structure and Written Expression session. Therefore, this program is considered very necessary to make a valuable contribution to the community, especially the students of SMK Telkom Pekanbaru. The stages carried out in the training process to complete Structure and Written Expression questions, among others: (1) The preparation stage for training activities. At this stage, community service activities regarding training for the completion of Structure and Written Expression questions for students of SMK Telkom Pekanbaru. (2) The training phases. At this stage, students are tested for their skills in mastering the Structure and Written Expression questions